2015
DOI: 10.3402/qhw.v10.25979
|View full text |Cite
|
Sign up to set email alerts
|

Communicating about eating behaviors. A qualitative study of Chilean women and their health-care providers

Abstract: Good communication between health care providers (HCPs) and patients is critical in achieving positive health outcomes. The purpose of this article was to compare the perceptions of Chilean woman and their HCPs with respect to determinants of eating behaviors. Semi-structured interviews were conducted with women (n=15) visiting a public health care center in Chile and with their HCPs (n=8) who were in charge of promoting healthy eating behaviors among women. Data from the interviews indicated similarities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…Further, participants thought that individuals should improve their dietary habits only after becoming ill. English and Chilean women share similar views. 42 43 Also, most of our participants reported that they cook separately (and healthily) only for family members who are sick. Despite their knowledge that oily and salty food is harmful to the heart, mothers appeared unaware of their own disease risk and hence maintained an unhealthy diet.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Further, participants thought that individuals should improve their dietary habits only after becoming ill. English and Chilean women share similar views. 42 43 Also, most of our participants reported that they cook separately (and healthily) only for family members who are sick. Despite their knowledge that oily and salty food is harmful to the heart, mothers appeared unaware of their own disease risk and hence maintained an unhealthy diet.…”
Section: Discussionmentioning
confidence: 87%
“…Other studies support these findings. 43 49 In addition, many mothers accused family members of interfering with their efforts to control the quality of their children's diets (eg, buying candy for the children). Young mothers in Western Australia reported the same barrier.…”
Section: Discussionmentioning
confidence: 99%
“…They shared that food containing chemical substance may cause the causes of dangerous diseases such as cancer. This finding is in contrast to a qualitative study of eating behaviours of Chilean women which found that although husbands were concerned about their family's nutrition, their actions as the controller of what foods were purchased meant that unhealthy food, for example, fatty foods, which are detrimental to the health of all in the family, were regularly purchased (Galvez, Valencia, Palomino, Cataldo, & Schwingel, 2015). For Muslims, eating good food is linked to Islamic teaching.…”
Section: Husbands Have Multiple and Variable Roles In Women's Health And Cancercontrasting
confidence: 74%